Combined in Vivo Bioluminescence and Fluorescence Imaging for Cancer Gene Therapy - J. D. Mocanu; E. H. Moriyama; M. C. Chia; J.-H. Li; K. W. Yip; D. P. Huang; C. Bastianutto; B. C. Wilson; F.-F. Liu (Molecular Imaging)
Nasopharyngeal carcinoma is intimately associated with the Epstein-Barr virus (EBV), which we have exploited therapeutically by constructing an EBV-specific synthetic enhancer sequence, within an adenoviral vector, denoted as adv.oriP. The achievement of tumor targeting provides therapeutic potential when delivered systemically, which could impact on distant metastases. We demonstrate here the feasibility and potential utility of combined, minimally invasive in vivo bioluminescence and fluorescence imaging to monitor adenoviral infection of subcutaneous C666-1 nasopharyngeal xenograft tumors stably expressing the DsRed2 gene. Fluorescence imaging was used to monitor the location and size of the C666-1. DsRed2 tumors, whereas bioluminescence imaging demonstrated the distribution and specificity of a transcriptionally targeted adenoviral vector, adv.oriP. fluc , expressing the firefly luciferase gene. Fluorescence, bioluminescence, and photographic images were aligned using grids to examine co-localization of adenovirus and tumors. Bioluminescence and fluorescence co-localized in 92% (11/12) of tumors at 24 hr and 100% (12/12) at 96 hr after adv.oriP. fluc (10 9 ifu) was administered intravenously. Nonspecific luciferase signal was detected in the liver area. The combined imaging was therefore successful in monitoring the uptake of systemically administered adenovirus in implanted tumors. This may ultimately lead to an effective noninvasive method to monitor the response of metastases to adenoviral gene therapy.